Climate Risk Profiles - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Fifteen Climate Risk Profiles were piloted in a phase 1, and has now been scaled out to an additional 16 Kenyan counties (31 counties in total), with 15 additional profiles under negotiation, and scaled out to Ethiopia, Tanzania, and the Philippines.